2021
DOI: 10.3390/foods10071499
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Extracts Obtained from Unripe Grapes and Evaluation of Their Potential Protective Effects against Oxidation of Wine Colour in Comparison with Different Oenological Products

Abstract: Unripe grapes (UGs) are a waste product of vine cultivation rich in natural antioxidants. These antioxidants could be used in winemaking as alternatives to SO2. Three extracts were obtained by maceration from Viognier, Merlot and Sangiovese UGs. The composition and antioxidant activity of the UG extracts were studied in model solutions at different pH levels. The capacity of the UG extracts to protect wine colour was evaluated in accelerated oxidation tests and small-scale trials on both red and white wines du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…This technique also takes advantage of the grapes removed by cluster thinning [114]. In addition to reducing alcohol content, Fia et al [115] also found that the addition of unripe grape fruit extracts to wine could play a role in protecting wine color during aging, and could be an interesting substitute for SO 2 during wine ageing. Considering that unripe fruits lack phenolic maturity, and bring an excess of astringency and herbaceous aromas, Junior et al [116] found that S. bacillaris can be used to increase glycerol content and malic acid degradation, thereby balancing the lack of palate fullness caused by low alcohol content and masking 'vegetative' odors.…”
Section: Ethanol Productionmentioning
confidence: 99%
“…This technique also takes advantage of the grapes removed by cluster thinning [114]. In addition to reducing alcohol content, Fia et al [115] also found that the addition of unripe grape fruit extracts to wine could play a role in protecting wine color during aging, and could be an interesting substitute for SO 2 during wine ageing. Considering that unripe fruits lack phenolic maturity, and bring an excess of astringency and herbaceous aromas, Junior et al [116] found that S. bacillaris can be used to increase glycerol content and malic acid degradation, thereby balancing the lack of palate fullness caused by low alcohol content and masking 'vegetative' odors.…”
Section: Ethanol Productionmentioning
confidence: 99%